A Multidisciplinary Approach to Managing Pelvic Floor Disorders: The Roles of Gynecology, Nursing, Health Education, Medical Physics, Laboratory Specialist, and Health Information Systems - Bshawri, Mazin Abdulrahman; Alnami , Majed Abdulrahman Ali; Jumah, Layla Abdullah Ahmed; Alhawaswi , Kawther Mahmoud; Almajid, Hamad Abdullah; Alshammari , Salma Mutlaq; Alghamdi, Kefayah Bakheet Mohammed; Walanshira, Jameela Mohamed Ali; Al-Halil, Majed Abdullah; Alojayan , Ghaiyah Ebrahim Abdullah; Mohammed, Khawlah Yahya Zakari; Alshreef, Bandar Saad (Journal of Ecohumanism, 2024)
Introduction: Pelvic floor disorders (PFDs) are a significant health problem among millions of people worldwide, especially among women. Due to the multifactorial etiology involving a component of musculoskeletal, neurological, hormonal and behavioral pathology, PFDs are complicated. For this reason, PFD management will require a very multidisciplinary approach and will need to integrate the expertise of different members of the healthcare discipline in providing patient centered multi-disciplinary care. Aim of work: To explore the multidisciplinary approach to managing pelvic floor disorders, focusing on the collaborative roles of gynecology, nursing, health education, medical physics, Laboratory Specialist, and health information systems. Methods: We conducted a comprehensive search in the MEDLINE database’s electronic literature using the following search terms: Multidisciplinary, Approach, Managing, Pelvic Floor Disorders, Roles, Gynecology, Nursing, Health Education, Medical Physics, Laboratory Specialist, and Health Information Systems. The search was restricted to publications from 2016 to 2025 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2025. The study was structured into various sections with specific headings in the discussion section. Conclusion: The management of pelvic floor disorders requires a multidisciplinary approach wherein several healthcare professionals may have a role to play. Gynecology has the diagnostic and interventional expertise, while nursing provides patient support and education. Medical physics provides resolution and aids in the selection of treatment options, and health education is raising awareness for promoting early intervention. Laboratory specialists also play a very important role in interpreting these imaging approaches, jointly working with clinicians linking radiologic findings to clinical symptoms. Health Information Systems afford the application of data-driven care promoting more efficient intercommunication and service access. In consort these specialties provide holistic, patient-centric care that proceeds to address the interplay of physical, psychological, and social aspects of pelvic floor disorders. On the application front, with more advancement in medicine, more application of new technology-based evidence within this multidisciplinary approach will surely elevate the quality of life for all concerned with PFDs.